A comparative biosorption study of sulfide (S-2) by using Lagenaria siceraria fruit based raw biosorbent (Bangladesh Journal of Scientific and Industrial Research, 2017)
In batch mode, the adsorption characteristics of S2- ions on Lagenaria siceraria mesocarp, pedicle and peel as raw materials have been studied in comparison to remove sulfide ions from tanneries waste water, under various parameters such as adsorbent dosage, contact time, agitation speed and pH. Maximum removal efficiency (70.96%) was observed on L. Siceraria peel followed by pedicle (51.58%) and mesocarp (29.57%) for adsorbent dosage of 0.10 g/L peel for 50 ml solution of sulfide (20 mg/L). The adsorption process was rapid, and it reached equilibrium in early 20-35 min for all adsorbents. Freundlich and Langmuir adsorption isotherms were employed for mathematical description of the adsorption equilibrium and to explain mechanism of adsorption. The maximum amounts of sulfide ions adsorbed, as evaluated by Langmuir isotherm, was 1.0436 mg/g of LS pedicle, 0.886 mg/g of peel and 0.843 mg/g of pedicle. The adsorption process conforms well to a pseudo second order kinetic model with best adsorption results at pH 8.Bangladesh J. Sci. Ind. Res. 52(4), 309-320, 2017